2023
DOI: 10.3390/w15061009
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of Water and Sediments of Harike Wetland with Phthalate Esters and Associated Risk Assessment

Abstract: Phthalate esters (PEs) are esters that are used as plasticizers and are widely known for their contamination and toxicological effects on various environmental matrices. The present study is designed to observe the co-occurrence of phthalate esters and their ecotoxicological and human health risk assessments on Harike wetland, Ramsar, a site recognized globally, is the largest freshwater wetland in Northern India. During the winter, summer, and monsoon seasons, samples of the water and sediments were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Alterations in the swimming behaviours and biochemical activities of zebrafish due to exposure to diheptyl phthalate and DiDP have also been reported [14]. Recent findings also revealed that exposure to DBP, BBP and DEP could lead to alteration in gamete quality, gene expression and have hormonal effects in various fish species [13,17,24]. Due to their toxicologically aggressive nature, their adverse effects are at the broad range of endpoint, even at much lower concentration levels than in most environmental studies [8,32].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Alterations in the swimming behaviours and biochemical activities of zebrafish due to exposure to diheptyl phthalate and DiDP have also been reported [14]. Recent findings also revealed that exposure to DBP, BBP and DEP could lead to alteration in gamete quality, gene expression and have hormonal effects in various fish species [13,17,24]. Due to their toxicologically aggressive nature, their adverse effects are at the broad range of endpoint, even at much lower concentration levels than in most environmental studies [8,32].…”
Section: Introductionmentioning
confidence: 94%
“…Due to their persistent, ubiquitous nature and ability to act as endocrine disruptors [8][9][10], PAEs have recently received much attention, both from many researchers and from various international organisations, such as the World Health Organization (WHO), the United States Environmental Protection Agency (USEPA) and the Stockholm Convention [2,[11][12][13]. The applications of PAEs in various industries, including agricultural (pesticides), household (cosmetics, personal care products, vinyl toys, food packaging and plastic wraps) and anthropogenic activities (incineration of fossil fuel, landfills, industrial and municipal effluents), are among the major sources of such compounds [2,3,8,[14][15][16][17]. Their ingression into the biosphere is frequently monitored, primarily due to their classification as emerging pollutants that are of prime environmental concern, with notorious potential to have known (documented) and unknown (undocumented) adverse toxicological effects on living organisms from sheer exposure to them [3,[18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recently, plastic honeycombs have been used to reduce the risk of melting the wax itself, resulting in reduced yield [15]. The European Union (EU) and the United States Environmental Protection Agency (USEPA) have listed six phthalates as priority toxic pollutants [16]. In 2023, the EFSA released the scientific opinion of public health risks associated with the presence of BPA in food, thus regulating its Tolerable Daily Intake (TDI) at 0.2 ng/kg bw /day [17].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the persistence and adverse effects on human health using OCPs and PCBs, some of these chemicals were banned or limited in many countries by the Stockholm Convention on Persistent Organic Pollutants, adopted in 2001 and entered into force in 2004 [10]. In 2005, the European Union identified 16 PAHs that possess both genotoxic and carcinogenic properties, 12 of which are also identifies to be definitely carcinogens for humans by the International Agency of Cancer (IARC) [11]. Nevertheless, due to uncontrolled and indiscriminate anthropogenic activities, residues of OCPs from agricultural practices, and trace of PCBs and PAHs are still persisted in the environment, accumulate in plants from polluted soil and pass into food, honey included [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recently, plastic honeycombs are used to reduce the risk of melting the wax itself, resulting in reduced yield [15]. The United States Environmental Protection Agency (USEPA) and the European Union (UE) have listed six phthalates as priority toxic pollutants [16]. In 2023, the EFSA has published the scientific opinion of public health risks related to the presence of BPA in food, thus regulating its Tolerable Daily Intake (TDI) [17].…”
Section: Introductionmentioning
confidence: 99%